Questioning the Language: A Review on Its Origin, Linguistics, and the Teaching of Language - Fikroni, Moh. Rofid; Hasanah, Wildatul (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2022)
This study aims to identify the language origin, linguistics, applied linguistics, the teaching of language ang the testing language. These scopes within the language serve a significant role in the language studies. Employing library research type, the data were collected through some books and article journals related to the topic of interests. Related to the origin of the language, some theories have been proposed that there is an innate capacity or some sort of mental device formed within human’s mind which responsible for the production of language. For such matter, the study of language, known as Linguistics, has been vastly developed to discuss and explain how language and its aspects work within the interactions done by humans in daily basis. The complexity of the language itself and its effect within human interaction serves one the most important aspects in the teaching of language and testing of language.